Pathogenic Mechanisms in Lupus Nephritis: Nucleosomes Bind Aberrant Laminin β1 With High Affinity and Colocalize in the Electron‐Dense Deposits. Issue 2 (February 2014) - Olin, Anders I.; Mörgelin, Matthias; Truedsson, Lennart; Sturfelt, Gunnar; Bengtsson, Anders A.
<x xml:space="preserve">Abstract</x> Objective Apoptotic nucleosomes are structurally and immunologically involved in lupus nephritis. The purpose of this study was to examine the expression and function of laminins and their interactions with nucleosomes in the kidneys of patients with lupus nephritis, using surface plasmon resonance (SPR) analysis. Methods SPR interaction analysis was used to quantify the strength of laminin–nucleosome interactions. Electron microscopy techniques were used to determine in vivo colocalization of IgG, chromatin, and laminin β1, as well as to characterize nucleosome–laminin interactions in vitro. Results Nucleosomes were found to possess high affinity for laminin β1–containing laminins and to have the potential to form stable molecular complexes with these structures. In vivo, laminin β1 was aberrantly expressed in the glomerular basement membrane (GMB) of lupus nephritis patients, and in situ, it acted as a nucleosome ligand, selectively colocalizing with nucleosomes within electron‐dense deposits (EDDs). Normal adult laminin 11, which contains laminin β2, did not bind nucleosomes, and it did not colocalize in vivo with the nucleosomes in the nephritic GBM. In addition, TGFβ1 was expressed by the glomerular mesangium, glomerular endothelial cells, and by podocytes in patients with lupus nephritis. It was trapped in situ within EDDs by an as‐yet‐unknown ligand. As was recently described in a transgenic mouse model, paracrine kidney glomerular TGFβ1 may thereby contribute to the development of glomerulopathy via the induction of laminin β1 incorporation in the GBM, whereas systemic blood vessel–derived TGFβ1 could be trapped during filtration. Conclusion Our findings of the specific high‐affinity binding of nucleosomes to aberrantly expressed laminin β1 in the GBM and their colocalization in the GBM may explain important features of the initial steps in the pathogenesis of lupus nephritis, the planted antigen hypothesis.